2021
DOI: 10.1080/14790718.2021.1985127
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinguistic influence in L3 acquisition across linguistic modules

Abstract: In this study, we investigated crosslinguistic influence (CLI) at developmental stages of third language (L3) acquisition of English by Russian-Norwegian children (N = 31). We tested seven linguistic properties within three linguistic modules (morphology, syntax and syntax-semantics). We compared the L3 learners to Norwegian (N = 90) and Russian (N = 74) second language (L2) learners of English. We predicted simultaneous facilitative and non-facilitative CLI in the L3 group within all modules, as the previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…If the L3 group scores in between the two L2 groups on either of the properties, and significantly differently from both groups, this can be interpreted as strong evidence in favor of cumulative activation of both previously acquired languages and combined (facilitative and non-facilitative) crosslinguistic influence. This is what is observed in Westergaard et al (2017), Jensen et al (2021), and Kolb et al (2022); see section 5.…”
Section: Choice Of Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…If the L3 group scores in between the two L2 groups on either of the properties, and significantly differently from both groups, this can be interpreted as strong evidence in favor of cumulative activation of both previously acquired languages and combined (facilitative and non-facilitative) crosslinguistic influence. This is what is observed in Westergaard et al (2017), Jensen et al (2021), and Kolb et al (2022); see section 5.…”
Section: Choice Of Propertiessupporting
confidence: 78%
“…More substantial evidence in support of the LPM and the Scalpel Model is reported in Jensen et al (2021) from the acquisition of L3 English by Norwegian-Russian bilinguals across three linguistic modules: syntax (word order), morphology (subject-verb agreement and copula) and the syntax-semantics interface (genericity and definiteness). In each domain, at least one condition targeted a property that was similar in Norwegian and English (while Russian was different) or similar in Russian and English (while Norwegian was different).…”
Section: Adverb Placementmentioning
confidence: 95%
“…This means that crosslinguistic influence can come from the L1, from the L2, or from both previously acquired languages. This has been argued, for example, by Listhaug et al (2021), who found influence from both L1 Norwegian and L2 English in L3 French, as well as by Westergaard et al (2017), Jensen et al (2021), and Kolb et al (2022), who found empirical evidence for simultaneous facilitative and nonfacilitative crosslinguistic influence in L3 English, both from a lexically similar language-Norwegian or German-and a more distant language-Russian-which shares a particular property with the L3.…”
Section: Property By Propertymentioning
confidence: 93%
“…(2017), Jensen et al. (2021), and Kolb et al. (2022), who found empirical evidence for simultaneous facilitative and nonfacilitative crosslinguistic influence in L3 English, both from a lexically similar language—Norwegian or German—and a more distant language—Russian—which shares a particular property with the L3.…”
Section: Background Literaturementioning
confidence: 98%
“…Westergaard (2021), Westergaard et al (2017), andJensen et al (2021) work within the Linguistic Proximity Model (LPM). This model has recently been espoused by ) using phonological data.…”
Section: Theoretical Backgroundmentioning
confidence: 99%